2001
DOI: 10.1053/jhep.2001.25545
|View full text |Cite
|
Sign up to set email alerts
|

A cellular gene up-regulated by hepatitis B virus–encoded X antigen promotes hepatocellular growth and survival

Abstract: Epidemiologic studies have identified a close link between chronic hepatitis B virus (HBV) infection and the development of hepatocellular carcinoma (HCC). 1,2 The most important risk factors for the development of HCC are the carrier state, characterized by persistent virus gene expression and replication, and the presence of chronic liver disease, which often progresses from active hepatitis to cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
(43 reference statements)
1
46
0
Order By: Relevance
“…As a first step, we used an alternative transcript of ABCC6, called URG7 (31), and showed that the expression level of this splice variant changes in parallel with that of ABCC6 upon the various stimuli (Fig. 5) strongly suggesting that the effect of ERK1/2 is transcriptional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step, we used an alternative transcript of ABCC6, called URG7 (31), and showed that the expression level of this splice variant changes in parallel with that of ABCC6 upon the various stimuli (Fig. 5) strongly suggesting that the effect of ERK1/2 is transcriptional.…”
Section: Discussionmentioning
confidence: 99%
“…To find out whether P-ERK1/2 acts at the transcriptional or the post-transcriptional level we made use of the URG7 transcript, a splice variant of ABCC6 ending in the 2nd intron of the gene (31). This short, truncated mRNA is transcribed from the same promoter as the ABCC6 transcript but have a different 3Ј-untranslated region leading to different post-transcriptional regulatory mechanisms (splicing and probably mRNA stability).…”
Section: Erk1/2 Activation Correlates With the Expression Level Of Abmentioning
confidence: 99%
“…Besides, the multi-functional X protein can transactivate a variety of viral and cellular promoter/enhancer elements, including up-regulating tumor necrosis factor-␣ gene expression in hepatocytes, which could induce intrahepatic inflammatory processes. 16 High replicative strains could also express more X protein in hepatocytes and cause liver injury indirectly. Mutations in the X protein could increase its transactivating effects and upregulate viral or cellular genes, resulting in hepatocellular growth and liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the X protein could increase its transactivating effects and upregulate viral or cellular genes, resulting in hepatocellular growth and liver injury. 16,17 "Hot-spots" mutations at nucleotides 1764 A3 T and 1766 G3 A in the core promoter and the precore 28th stop mutation have been described as associated with more severe hepatitis. 18 In our study, all isolates had at least 1 of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The strong epidemiologic relationship between chronic HBV infection and HCC [2,3], and the important contribution of HBx to HCC [22][23][24][25][26], suggest that the molecular pathways altered by HBx are important for tumor development [26]. Previously, HBx has been shown to alter the expression of genes that promote hepatocellular growth, survival, and tumorigenesis [16][17][18][19][20]. These up-regulated proteins appear to trigger corresponding antibody responses that may accompany the onset of critical transforming events.…”
Section: Discussionmentioning
confidence: 99%